A multi-mode triboelectric nanogenerator for energy harvesting and biomedical monitoring. (February 2022) - Wu, Yuxiang; Li, Yusheng; Zou, Yang; Rao, Wei; Gai, Yansong; Xue, Jiangtao; Wu, Li; Qu, Xuecheng; Liu, Ying; Xu, Guodong; Xu, Lingling; Liu, Zhuo; et al.
Abstract: In the field of exercise physiology, it is of great significance to monitor human body motion status and physiological functions for assessing physical quality and training load. However, the wearable electronics as the mainstream monitoring solution have power consumption and bulk-size issues that limit sustainable operation. Here, we present a multi-mode stretchable and wearable triboelectric nanogenerator (msw-TENG) for biomechanical energy harvesting and physiological functions sensing. The msw-TENG fabricated by a liquid metal and silicone achieves stretchable and highly conductive characteristics at the same time, and realizes conformal contact with skin. The msw-TENG mainly includes contact separation/stretch/press modes, which can be randomly transformed according to the actual applications. The device converts the biomechanical energy of limb movement into electrical energy for directly lighting up commercial LEDs. Additionally, the radial artery pulse signal, joint bending angle and limb stability can be detected in real-time. As a multifunctional biomedical active sensor that is exempt from needing an extra power source, the proposed msw-TENG holds great potentials in the future of exercise monitoring and rehabilitation therapy. Graphical Abstract: A multi-mode stretchable and wearable triboelectric nanogenerator (msw-TENG) base on liquid metal and silicone for biomechanical energy harvesting and physiological functions sensing. ga1 Highlights: The msw-TENG includes contact separation/stretch/press modes for establishing a multifunction self-powered system. An ingenious design of the island-bridge of the liquid metal realizes ultra-sensitive response to small tension and pressure. The thickness of msw-TENG is controlled to be pliable enough to closely fit the surfaces of the skin.